Pemberdayaan UMKM Digital Tingkat Desa : Pengabdian KKN Melalui Pendampingan Digitalisasi UMKM di Desa Gaum, Tasikmadu, Karanganyar - Bambang Hadinugroho; Brillian Raiszhul Firdaus (Universitas Kristen Indonesia Toraja, 2023)
Kuliah Kerja Nyata (KKN) is a real implementation of the responsibilities of lecturers and students in carrying out the Tri Dharma of Higher Education, especially in the aspect of community service. This activity focuses on the involvement of universities with the Gaum village community, with the main objective of increasing community understanding of financial literacy and digitalization of Micro, Small and Medium Enterprises (MSMEs) in the digital era. Community service activities are carried out through various programs, including surveys of MSMEs, counseling on digitalization and financial literacy, socialization of financial protection, and guidance to MSMEs. The results of these activities indicate an increase in community spirit and understanding, especially MSME players in Gaum village, in managing financial aspects and utilizing digital platforms for marketing. Thus, this KKN creates a positive synergy between universities and local communities, supporting the development of micro-economies in the current digital era.